The Asymmetric Impact of Weighting Economic and Political Events on the Fluctuations of Banking Group Index (Case of Tehran Stock Exchange) - Seyed Hossein Mirjalili; Saeed Dehghan Khavari; Maryam Iraji (Journal of Money and Economy, 2021)
Stock Exchange Investors have paid more attention to the banking group in recent years so that in many cases, the direction of the banking index has changed the general direction of the market. Therefore, exploring the banking index fluctuation is important from the point of view of investors as well as the direction of the market. The purpose is to examine the effectiveness and direction of news, as one of the most important factors in the formation of volatility, on the banking group index in Tehran Stock Exchange by using 1460 daily records during 2018-2019 and the GARCH family's method. The data were collected for four different newsgroups, including economic, political, psychological, and financial. After that, the news that had more relationship with the banking group was separated to underscore in the weighting stage and divided into the positive and negative news, according to the perspectives of capital market experts and economic elites. The results indicated that newsgroups have a significant effect on the group index, and only the negative political model on the banking group has an asymmetric effect. The results indicated that political and economic news has a positive and significant impact on banking index fluctuations.
Keywords: 330; Capital Market; Banking Group Index; Economic and Political Event; Asymmetric Effect; Exponential GARCH